Biostatistics : How it works - Steve Selvin (Pearson Education, 2005)
Aims to provide an introduction of how statistics works at a beginning level. Every concept is explained, along with a mathematical/statistical justification, and then illustrated by at least one worked data example. This text allows readers to acquire the ability to understand complicated statistical issues, such as linear regression theory.